NUTQ TA’SIRCHANLIGINI OSHIRISH USULLARI - Yuldashev Avaz Jumayevich (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: This article provides information on how to increase the effectiveness of speech and the effectiveness of using these methods.